A Comparative Study of Student’s Perception in Linear System Course: Face-to-Face and Online Distance Learning (International Journal of Academic Research in Progressive Education and Development, 2022)
The perceptions and interactions of students impact the efficacy of online learning. When measuring the success of ODL courses, it is best to use the survey approach, which allows each side of the perspective, such as the teacher, students, and employers, to be recorded. In this study, students' perceptions of course content, lecturer professionalism, teaching and learning activities, and infrastructure were compared across three teaching delivery modes. Once measuring the success of the courses, it is best to use the survey approach. This study employed Introduction to Linear System courses for the Electrical Engineering students, and the survey was acquired through an official university's student feedback system known as SuFO. The relationship between the student's perception and delivery modes was examined using the statistical methods Chi-Square, Phi, and Cramer's V, which revealed a weak relationship between them. This study can assist lecturers to discover deficiencies in their delivery methods and enhancing their abilities over time.
Keywords: Online Distance Learning (ODL), Students’ Perception, Student Feedback Survey, Statistical Method, SPSS.